Comparison Of Student’s Learning Achievement On Population And Environmental Education Courses Through Implementation Of Problem Based Learning Model And Direct Instruction Model - Rissa Megavitry (Departement of Mathematics Education, 2022)
This research is a quasi-experimental research which aimed to determine the influence of Problem Based Learning Model and Direct Instruction model to student’s learning achievement of students of Family Welfare Education Major. This research was using The Static Group Pretest-Posttest Design. The research was conducted for three sessions. Data collecting technique in this research was using the instrument which was the multiple choice evaluation tests. Data analysis was using descriptive statistic and inferential statistic with covariance test. By the analysis result, it can be conclude that, (1) student’s learning achievement which taught by implementation of Problem Based Learning model is in good category, with average value is 81,47; (2) student’s learning achievement which taught by implementation of Direct Instruction model is in good category, with average value is 77,60; (3) There are differences in the learning achievement students of Family Welfare Education Major on Population and Environmental Education Courses taught by implementation of Problem Based Learning Model and Direct Instruction Model